2022
DOI: 10.1101/2022.03.13.484119
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

N-Terminomic Changes of Neurons During Excitotoxicity Reveal Proteolytic Events Associated with Synaptic Dysfunctions and Inform Potential Targets for Neuroprotection

Abstract: Excitotoxicity is a neuronal death process initiated by over-stimulation of ionotropic glutamate receptors. Although dysregulation of proteolysis and protein phosphorylation signaling networks is critical for excitotoxicity, the identity of affected proteins and mechanisms by which they induce neuronal cell death remains unclear. To address this, we used quantitative N-terminomics to identify proteins modified by proteolysis in neurons undergoing excitotoxic cell death. Our investigation led to the discovery o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 113 publications
(206 reference statements)
1
11
0
Order By: Relevance
“…Recently, another pathological regulatory mechanism of CaMKII was described, which could contribute to the hyperactivity of a subpopulation of CaMKII after ischemia. Specifically, CaMKII was found to be proteolytically processed by the protease calpain after ischemia, which generates a stable kinase fragment with uncontrolled kinase activity (∆CaMKII, 31 kDa) [ 34 , 113 ]. As the cleavage site was mapped to the beginning of the regulatory domain (i.e., M 281 ↓H 282 ), cleavage of CaMKII at this site generates a N-terminal fragment consisting of the kinase domain only ( Figure 4 ).…”
Section: Disturbances In Camkiiα Signaling After Ischemic Strokementioning
confidence: 99%
See 4 more Smart Citations
“…Recently, another pathological regulatory mechanism of CaMKII was described, which could contribute to the hyperactivity of a subpopulation of CaMKII after ischemia. Specifically, CaMKII was found to be proteolytically processed by the protease calpain after ischemia, which generates a stable kinase fragment with uncontrolled kinase activity (∆CaMKII, 31 kDa) [ 34 , 113 ]. As the cleavage site was mapped to the beginning of the regulatory domain (i.e., M 281 ↓H 282 ), cleavage of CaMKII at this site generates a N-terminal fragment consisting of the kinase domain only ( Figure 4 ).…”
Section: Disturbances In Camkiiα Signaling After Ischemic Strokementioning
confidence: 99%
“…Although proteolytic processing of CaMKII by calpain could already be described in vitro in 1989 [ 116 , 117 , 118 ], its relevance in vivo was only recently addressed. Intriguingly, ∆CaMKII has been detected exclusively after ischemic stroke (photothrombotic stroke) [ 113 ]. Furthermore, in vitro experiments showed that proteolytic processing of CaMKII at this site requires prior Ca 2+ -stimulation and Thr286 autophosphorylation [ 113 ], resembling ischemic conditions of CaMKII [ 26 ].…”
Section: Disturbances In Camkiiα Signaling After Ischemic Strokementioning
confidence: 99%
See 3 more Smart Citations